Broadband spectrum based on mechanically induced cascaded long-period fibre gratings - Veeriah, S.; Faidz, A. R.; Phua, Y. N.; Mishra, V. (2005)
A simple and efficient variable optical attenuator (VOA) is achieved by using microbend gratings on single-mode fiber (SMF). The flatness of the attenuator is maintained for 100 nm along the C+L band spectrum. Controlling the pressure will vary the attenuation depth of the device. (C) 2005 Wiley Periodicals, Inc.